Synthesis, mesomorphic and physical properties of two new analogs of Schiff's base with an alkenic terminal chains - Yilmaz-Canli, Nimet; Bilgin-Eran, Belkis; Nesrullajev, Arif (ELSEVIER, 2011)
Characterization and investigation of the physical properties of two new analogs of salicylaldimine compounds, which were synthesised for the first time by our group, are reported in this work. 5-(10-undecenyloxy)-2-[[[4-hexylphenyl]imino]methyl]phenol and 5-(10-undecenyloxy)-2-II[4-hexyloxyphenyl]imino]methyl]phenol have been studied. Different degree of mesomorphism has been found in these analogs. Typical textures and temperatures of the direct and reverse phase transitions, taking place in these analogs, are presented. Temperature dependences of the optical transmission for both heating and cooling are given. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Liquid crystals; Salicylaldimine compounds; Textures; Phase transition; Optical transmission; LIQUID-CRYSTALLINE PROPERTIES; ORIENTATIONAL PROPERTIES; ISOTROPIC-PHASE; COPPER-COMPLEXES; MEAN-FIELD; TRANSITION; BEHAVIOR; TRANSFORMATIONS; TEMPERATURE; COMPOUND; Chemistry